"The art of imposing measurement upon the mind": Sir Francis Galton and the genesis of the psychometric paradigm. (June 2022) - Michell, Joel
Sir Francis Galton singlehandedly instigated the navigational settings for the discipline of psychometrics by presupposing that mental attributes are measurable. In turn, this presupposition became the defining pillar of the psychometric paradigm. There were no scientifically sound reasons for adopting this presupposition and those Galton gave beg the question every time. So, what drove him to endorse this presupposition? Two considerations steered him in this direction: first, his Pythagorean philosophy of science according to which measurement is a necessary feature; and second, his desire to present eugenics as a science, which, given his Pythagorean vision, entailed that eugenics must involve measurement of relevant mental attributes. The quantitative presupposition guiding psychometrics throughout its history was, therefore, a spin-off from Galton's marketing strategy for the pseudoscience of eugenics.